EVALUATION OF THE MERDEKA CURRICULUM IN ISLAMIC EDUCATION USING GOAL-FREE EVALUATION: AN ANALYSIS OF INSTRUCTIONAL AND NON-INSTRUCTIONAL IMPACTS ON STUDENTS’ DEVELOPMENT - Febriani Suci Islamiati; Asrori Asrori; Mukhammad Bakhruddin (Al-Mudarris: Journal Of Education, 2025)
This study examines the implementation of the merdeka curriculum in Islamic education at SD Muhammadiyah 21 Surabaya within the context of Indonesia’s ongoing educational reform. The research aims to evaluate both instructional and non-instructional impacts of the curriculum on students’ holistic development. The study was conducted in response to limitations of previous evaluations that relied heavily on goal-oriented models and tended to overlook unintended learning outcomes, particularly in moral and spiritual domains. A qualitative evaluative approach employing a Goal-Free Evaluation (GFE) model was used to identify actual outcomes experienced by students without reference to predefined curriculum objectives. Data were collected through in-depth interviews, classroom and school-wide observations, and document analysis. The findings reveal that the merdeka curriculum fosters increased learning engagement, deeper religious understanding, and enhanced ethical reasoning at the instructional level. Additionally, significant non-instructional impacts emerged, including character formation, spiritual awareness, discipline, and social competence, largely shaped by school culture, religious habituation, and co-curricular activities.